Anisotropy Gradients in the Middle of the Ross Sea Embayment, West Antarctica: Evidence From QL Scattered Surface Waves - W. Cheng; X. G. Hu; L. T. Liu (Geophysical Research Letters)
Abstract Long‐period quasi‐Love (QL) waves in West Antarctica were detected using the band‐pass filtering. Rayleigh waves from March 11, 2011 Tohoku Mw 9.1 earthquake and March 9, 2011 Tohoku Mw 7.3 earthquake had evident QL waves in the frequency range of 7–13 mHz when crossing the Ross Sea Embayment (RSE), while exhibiting normal behavior when crossing the Southern Ocean adjacent to the RSE. We located an anisotropic boundary in the upper mantle beneath the RSE according to the QL waves. Surprisingly, the boundary was consistent with the sharp transition zone of magnetic anomalies discovered by the most recent airborne magnetic surveys. Thus, we speculate that the anisotropic boundary was most likely due to vertical mantle flow below the RSE, which may provide evidence of a vertically coherent boundary condition in the RSE. That anisotropic boundary may be an important tectonic imprint for maintaining the stability of the Ross Ice Shelf.